Global burden of metabolic diseases: data from Global Burden of Disease 2000-2019. A cosortium of metabolic disease. (25th January 2023) - Chew, N; Ng, C H; Tan, D; Kong, G; Lin, C X; Chin, Y H; Foo, R; Chan, M; Muthiah, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The growing prevalence of metabolic diseases is a major concern. We sought to examine the global trends and mortality of metabolic diseases using estimates from the Global Burden of Diseases, Injuries and Risk Factors Study (GBD) 2019. Methods: Global estimates of prevalence, deaths, and disability-adjusted life year (DALYs) from 2000-2019 were examined for metabolic diseases (type 2 diabetes mellitus [T2DM], hypertension, and nonalcoholic fatty liver disease [NAFLD]). For metabolic risk factors (hyperlipidemia and obesity), estimates were limited to mortality and DALYs. Death rates was compared across sex, World Health Organisation regions and Socio-demographic Index (SDI) quintiles. Age-standardised prevalence and death rates were presented per 100, 000 population with 95% uncertainty intervals (UI). Findings: From 2000 to 2019, prevalence rates increased for all metabolic diseases, with the most pronounced increase in high SDI countries. In 2019, the mean (95%UI) age-standardised prevalence per 100, 000 population was estimated to be 15, 023 (13, 493-16, 764) for NAFLD, 5, 283 (4, 864–5, 720) for T2DM and 234 (171-313) for hypertension. The highest age-standardised death rates were observed in obesity (62·59 [39·92-89·13]; males, 66·55 [39·76-97·21]; females. 58·14 [38·53-81·39]), followed by hyperlipidemia (56·51 [41·83-73·62]; males, 67·33 [50·78-86·43]; females, 46·50 [32·70-62·38]), T2DM (18·49 [17·18-19·66], males, 67·33 [50·78-86·43]; females, 46·50 [32·70-62·38]), hypertension (15·16 [11·20-16·75]; males, 14·95 [10·32-16·75]; females, 15·05 [11·51-17·09]) and NAFLD (2·09 [1·61-2·60]; males, 2·38 [1·82-3·02]; females, 1·82 [1·41-2·27]). Mortality rates decreased over time in hyperlipidemia (-154%), hypertension (-52%) and NAFLD (-52%), but not in T2DM and obesity. The highest mortality for metabolic diseases was found in Eastern Mediterranean, and low to low-middle SDI countries. Conclusion: The global prevalence of metabolic diseases has risen over the past two decades regardless of SDI. Attention is needed to address the unchanging mortality rates attributed to metabolic disease and the regional, socioeconomic, and sex disparities in mortality from metabolic disease. Figure 1A) Deaths, 1B) DALYs Figure 2. Proportion of Deaths